(untitled) (The Pakistan Development Review, 2016)
The study used data from 3298 food crop growers in Pakistan. Potential outcome treatment effects model was applied to evaluate the impact of adaptations on household food security. A household Food Security Index (FSI) was constructed applying Principle Component Analysis (PCA). Adaptation strategies employed by the farmers in response to climate change were categorised into four groups namely: changes in sowing time (C1); input intensification (C2); water and soil conservation (C3); and changes in varieties (C4). Out of 15 mutually exclusive combinations constructed for evaluation, only 7 combinations were considered for estimating the treatment effects models because of limited number of observations in other cases. Results of only two of the 7 are discussed in the paper, as the other 5 had very small number of adapters and the impact measures shown either insignificant results or had opposite signs. The first (C1234) combined all the four, while the second (C234) combined the last three strategies. The results suggest that the households which adapted to climate changes were statistically significantly more food secure as compared to those who did not adapt. The results further show that education of the male and female heads, livestock ownership, the structure of house—both bricked and having electricity facility, crops diversification, and non-farm income are among the factors, which raise the food security of farm households and their impacts are statistically significant. The variables which are significantly negatively associated with the food security levels include age of the head of household, food expenditure management, households having less than 12.5 acres of land— defined as marginal (cultivate 6.25 to 12.5 acres). Farmers of cotton-wheat, rice-wheat, and rain-fed cropping systems are found to be more food secure as compared to the farmers working in the mixed cropping systems where farm holdings are relatively small and high use of tube-well water adding to salinity of soils. It is crucial to invest in the development of agricultural technological packages, addressing issues of climate change relevant to different ecologies and farming systems; improve research-extension-farmer linkages; enhance farmers‘ access to new technologies; improve rural infrastructure; development of weather information system linking meteorological department, extension and farmers; and establishment of targeted food safety nets as well as farm subsidy programs for marginal farm households.